Lupclip: Annual mowing has the potential to reduce the invasion of herbaceous Lupinus polyphyllus - Ramula, Satu (Dryad, 2020)
In order to manage invasive plant species efficiently, it is necessary to
have a thorough understanding of different strategies of population
control, including the underlying mechanisms of action and the
consequences for target populations. Here, I explored the effectiveness of
biomass removal as a method of control for the invasive perennial herb
Lupinus polyphyllus. More specifically, using seed material from 11
populations, I assessed among-population variation (if any) in plant
compensatory growth as a response to annual biomass removal under
standardised growing conditions over two consecutive years, and quantified
the demographic effects of a single biomass-removal event. In all study
populations, annual biomass removal reduced plant size, flowering
probability, and shoot and root biomass. Biomass removal also reduced
plant survival and the number of flowering shoots, but these effects were
pronounced at certain time points only. A population-level demographic
analysis revealed that a single biomass-removal event considerably
decreased the long-term population growth rate (λ); this decline in λ was
due to a reduction in plant fecundity followed by survival and growth.
These findings suggest that annual mowing has the potential to curb
invasions of L. polyphyllus because plants are not able to fully
compensate for drastic biomass loss.
This dataset of Lupinus polyphyllus was collected based on a common garden
study in the Ruissalo Botanical Garden of the University of Turku, Finland
during 2017-2018. Individuals that died before the first clipping
treatment in June 2017 (n = 40 individuals out of 880) have been deleted
from the data.
Lupclip_README.txt: Readme file a detailed description of the
variables in each file. Lupclip_time.xlsx: Measurements of individual
plants of Lupinus polyphyllus in four time points. Lupclip_biomass.xlsx:
Plant dry biomass at the end of the experiment. Lupclip_IPMdata.xlsx:
Demographic data of Lupinus polyphyllus from two consecutive years.
Lupclip_IPM.txt: An R-code to construct an integral projection model and
calculate the deterministic population growth rate with 95% confidence
intervals based on bootstrapping.